Implementation of GPVR and its Comparison with GPSR: Advancements in Vehicle Ad-Hoc Networks (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the past few years, VANETs, because of their unmistakable societal impact that promises to revolutionize the way we drive, various car manufacturers, government agencies and standardization bodies have spawned national and international consortia devoted exclusively to VANET. Indeed, the fact of being networked together promotes car-to-car communications, even between cars that are tens of miles apart.